TES KEMAMPUAN GRAMATIKA DALAM PEMBELAJARAN BAHASA INDONESIA - Henny Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
Grammar evaluation focuses on grammatical competence, namely mastery of linguistic code, ability to remember vocabulary, morphology, syntax, and phonological characteristics of a language and manipulate these characteristics to form words and form sentences. In choosing the grammar test, four things need to be considered, namely (1) level and type of school, (2) curriculum and grammar test book, (3) test objectives (4) language status taught. The form of grammar tests, namely subjective tests and objective tests, namely subjective tests and objective tests. Grammar tests aim to determine the level of students' initial abilities, diagnose student learning difficulties, know the development of students' abilities, know the development of students' abilities, encourage teachers to carry out learning activities better, know the results of learning, encourage students to learn, and know the achievement of the curriculum. In the implementation the teacher uses the form of tests that are subjective tests which can be in the form of bounded description tests and free descriptions that refer to cognitive levels including multiple choice forms, forms of memory errors, forms of rearrangement, forms of completing, transformation, changing words, broken sentences, matchmaking, matching, merging and additions. This test requires students to be able to connect facts and concepts, organize them in logical coherence and then pour the results of their thoughts into written expressions. Objective tests are tests that demand or require students to only give short answers, even just by choosing a specific code that represents an alternative answer that has been prepared.